Blended waste rock, tailings and slag to produce cover systems for closure - G. Ward Wilson (Instituto de Ingenieros de Minas del Peru, 2005)
Waste rock and tailings may be combined through intimate blending to create new materials with superior physical and hydraulic properties. The new material, termed Co-Mix, has high shear strength characteristics, low compressibility, low hydraulic conductivity, and a high water retaining capacity. Co-Mixed tailings and waste rock may be used to construct cover systems, internal barriers and seals, confinement structures and full depth waste repositories. Field scale test trials using Co-Mixed blends of waste rock, tailings and slag have been constructed at the Copper Cliff Mine in Sudbury, Canad. These lysimeters will be used to evaluate the performance of the new material for cover systems that may potentially be constructed on the tailings impoundment upon closure. In this sense, the paper point out the construction of the lysimeters with respect to expected field performance during the spring snow melt period and summer to produce cover systems for closure.